Unveiling the effects of electric field treatments on crop cultivation: a game-changing sustainable energy strategy for plant pathogen eradication and boosting yield growth in agriculture, validated with an artificial intelligence approach - S.S. Jayakrishna; S. Sankar Ganesh (Energy Nexus)
Discovered novel energy contact patterns in agriculture for banana crop cultivation, the power of electro-culture-based electrified farming witnessed the incredible results of plant pathogen control, which boosts banana yield growth and enhances food safety. Project E-Grow involves real-time agricultural practices, providing electrical conductivity to crops for 9 h/Day for 275 days up to the final harvest. The electrified Triangular Farming (ETF) approach delivers the effects of electrical phenomena on the termination of pathogenic nematodes. The results are validated through a computer vision-based model that improved YOLO-v8 by redesigning the c2f function and employing deep learning techniques with a self-developed Banana Pathogenic Nematode (BPN) dataset. This model achieved a precision of 85 %, a recall of 87.3 %, and an mAP50 of 81 %, scoring highly in comparison to other versions of YOLO-v8n, m, and l size. The experiment included two different (T) treatments based on power energization contact with crops. T1 used Static Electricity Treatment (SET) and T2 employed Rhizosphere Electrode Treatment (RET) with anode and cathode terminals inserted into the soil. The direct power discharging throughout the plant and soil protects the crop from parasite invasion. Significant protein increases were observed in Dissolved Organic Matter (DOM) analysis on electrified banana plants. Further, the electrified plants produced early flowering fruit bunches faster and healthier than those in non-treated (control) zones. Live controlled by the Internet of Things (IoT) using microscopy image analysis and Programmable DC Power Supply (PDPS) digital data. Comprehensively, this study discloses various electric patterns and aids farmers in employing electrified cultivation cost-effectively, offering a promising future for agriculture.